Roald Amundsen's Belgica diary : the first scientific expedition to the Antarctic - Amundsen, Roald; Decleir, Hugo (Red.) (Bluntisham Books, 1999)
Keywords: Antarktis; Belgica (skip); Roald Amundsen; Sydpolen; dagbok; oppdagelsesreiser; overvintring; polarekspedisjoner; vitenskap

Roald Amundsen conquers the South Pole - Berg, Kåre (Norwegian maritime explorers and expeditions : over the past thousand years, 1999)
Keywords: Antarktis; Fram (skip); Sydpolsekspedisjonen; oppdagelsesreiser

C.A. Larsen - Pioneer of the Antarctic ocean - Devig, Thor N (Norwegian maritime explorers and expeditions : over the past thousand years, 1999)
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; Sørishavet; historie; hvalfangst; kartlegging; oppdagelsesreiser; pelagisk; polarekspedisjoner

Søylegangen i Buenos Aires - Fløgstad, Kjartan (Eld og vatn : nordmenn i Sør-Amerika, 1999)
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; Roald Amundsen; hvalfangere; hvalfangstindustri; oppdagelsesreiser; pelagisk

Dagboken fra Belgica-ekspedisjonen 1897-99 : Roald Amundsens første ferd til Antarktis - Amundsen, Roald (Vågemot miniforl., 1998)
Keywords: Antarktis; Belgica (skip); Roald Amundsen; dagbøker; oppdagelsesreiser; overvintring; polarekspedisjoner; vitenskap

Roald Amundsen : en biografi - Bomann-Larsen, Tor (Cappelen, 1998)
Keywords: Antarktis; Nordmenn; Roald Amundsen; Sydpolen; biografi; ekspedisjoner; oppdagelsesreiser

Noruega y las regiones polares - Hansson, Rasmus (Real Ministerio Noruego de Asuntos Exteriores, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Norvegija i poljarnye rajony - Hansson, Rasmus (Izdano Ministerstvom inostrannych del Norvegii, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Norway and the polar regions - Hansson, Rasmus (The Royal Norwegian Ministry of Foreign Affairs, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Norwegen und die Polargebiete - Hansson, Rasmus (Kgl. Norwegisches Ministerium für Auswärtige Angelegenheiten, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Klarius Mikkelsen's 1935 landing in the Vestfold Hills, East Antarctica: some fiction and some facts - Norman, Frederick Ian; Gibson, John A E; Burgess, J S (Polar Record, 1998)
Exploratory activities of Norwegians, particularly those directed by Lars Christensen, off eastern Antarctica are discussed briefly in relation to contemporary Antarctic investigations and politics. The interests of Norway there and Christensen's role in establishing an understanding of the local coastline are indicated. Particular attention is paid to the landing made by Klarius Mikkelsen in the Vestfold Hills, East Antarctica, on 20 February 1935. Note is taken of the site's recent re-discovery, and the symbolic role of the landing in the national aspirations of Norway, Britain, and Australia is discussed. Mikkelsen operated under commercial and scientific interests promoted by Christensen, and his landing was, at least in published material, seen as an extension of them. However, there is a suggestion that not only had a new Norwegian land been discovered, and a landing made, but that a claim to it was at least considered. Such a claim was not appropriate given previous agreements between Norway and Britain. The site's location and environs are discussed, as are subsequent flights over it and visits made there by Australian expeditioners. The ambiguity associated with claims that Caroline Mikkelsen was the first woman to land on the Antarctic mainland is also examined. Since Mikkelsen's site was on an island within the Tryne Group, to the north of Davis station, if a mainland location is required to establish such an event, then an alternative (Scullin Monolith) is proposed; however, on this occasion four women were involved, but who was first ashore remains uncertain.
Keywords: Antarktis; Nordmenn; Thorshavn ekspedisjon; første landgang; kvinner; oppdagelsesreiser

Sydpolen - Skattum, Ole Jacob (Roald Amundsen som geografisk oppdager, 1998)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser

Døde menn vender tilbake: Shackletons høyst private Whitbread-seilas - Winge, Jon (Norsk sjøfartsmuseum. Årbok, 1998)
Keywords: Endurance (skip); Ernest Henry Shackleton; Sørishavet; ekspedisjoner; oppdagelsesreiser; skipsfart

In To the South Pacific and On To Antarctica - Feeney, Robert E (Polar journeys : the role of food and nutrition in early exploration, 1997)
Keywords: Antarktis; Belgica ekspedisjon; Frederick Cook; Roald Amundsen; ernæring; mat; oppdagelsesreiser

The Quest for the South Pole: Successes and Deaths - Feeney, Robert E (Polar journeys : the role of food and nutrition in early exploration, 1997)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; ernæring; mat; oppdagelsesreiser

Dagboksnotater fra Sydpolen - Hassel, Sverre (Vågemot miniforl., 1997)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Den tredje mann : beretningen om Hjalmar Johansen - Kvam, Ragnar (Gyldendal, 1997)
Keywords: Antarktis; Nordmenn; Sydpolsekspedisjonen; biografier; oppdagelsesreiser; polarekspedisjoner; polarhistorie

Belgica-ekspedisjonen : et hundreårsminne - Lie, Svein B (Norvegiana Nytt, 1997)
Keywords: Antarktis; Belgica ekspedisjon; forskning; oppdagelsesreiser; polarekspedisjoner

Dagbok fra Sydpolen - Johansen, Hjalmar (Vågemot forl., 1996)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Cato mot Sydpolen - Hauge, Odd Harald; Bry, Knut; Ebbesen, Lars (Pax, 1995)
Keywords: Antarktis; Nordmenn; Sydpolen; ekspedisjoner; fotokunst; funksjonshemmede; oppdagelsesreiser; polarekspedisjoner; reiser; reiseskildringer

The Vestfold Hills: the Norwegian connection - Patterson, D (ANARE News, 1995)
Keywords: Antarktis; Nordmenn; ekspedisjoner; oppdagelsesreiser

Before the heroes came : Antarctica in the 1890s - Baughman, Timothy H (University of Nebraska Press, 1994)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Southern Cross; ekspedisjonen; oppdagelsesreiser; polarhistorie

Moje życie polarnika - Amundsen, Roald; Thylwe, Halina (Iskry, 1993)
Keywords: Antarktis; biografi; ekspedisjoner; oppdagelsesreiser; polarområdene

Geographical discoveries in Antarctica by the whaling industry - Headland, Robert Keith (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Antarktis; Carl Anton Larsen; Lars Christensen; ekspedisjoner; geografi; hvalfangst; oppdagelsesreiser

Into the heart of the Antarctic - Imbert, Bertrand C (North Pole, South Pole : journeys to the ends of the earth, 1992)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser

Sandefjord - et naturlig polarforskningssenter - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1991)
Keywords: Antarktis; Norsk Polarinstitutt; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Nankyoku ten - Amundsen, Roald; Nakada, Osamu (Dorufin Press, 1990)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

I hjertet av Antarktis; Norge i Antarktis - Imbert, Bertrand C; Hem, Arne (Polarforskningens pionerer, 1990)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; Roald Amundsen; Sydpolsekspedisjonen; Sørishavet; hvalfangst; oppdagelsesreiser